10(x+4)-3(2x+5)-1=10

Simple and best practice solution for 10(x+4)-3(2x+5)-1=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10(x+4)-3(2x+5)-1=10 equation:


Simplifying
10(x + 4) + -3(2x + 5) + -1 = 10

Reorder the terms:
10(4 + x) + -3(2x + 5) + -1 = 10
(4 * 10 + x * 10) + -3(2x + 5) + -1 = 10
(40 + 10x) + -3(2x + 5) + -1 = 10

Reorder the terms:
40 + 10x + -3(5 + 2x) + -1 = 10
40 + 10x + (5 * -3 + 2x * -3) + -1 = 10
40 + 10x + (-15 + -6x) + -1 = 10

Reorder the terms:
40 + -15 + -1 + 10x + -6x = 10

Combine like terms: 40 + -15 = 25
25 + -1 + 10x + -6x = 10

Combine like terms: 25 + -1 = 24
24 + 10x + -6x = 10

Combine like terms: 10x + -6x = 4x
24 + 4x = 10

Solving
24 + 4x = 10

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-24' to each side of the equation.
24 + -24 + 4x = 10 + -24

Combine like terms: 24 + -24 = 0
0 + 4x = 10 + -24
4x = 10 + -24

Combine like terms: 10 + -24 = -14
4x = -14

Divide each side by '4'.
x = -3.5

Simplifying
x = -3.5

See similar equations:

| 112-5x=10x-22 | | b+2a+4c=b | | 1/4x+1/3x+5/6=15/4 | | -8-3=12-8x | | 2r^2-2r-1=0 | | 8+5*lnx-22.6=0 | | 14x-14=0 | | 13-10x=127-32x | | 6-10x=57-31x | | 13-10x=17-32x | | b+2a+4c= | | 3x+4(x-6)+3=0 | | 5/x^3(3x^8) | | x+(17x-18)=90 | | 3p+5=11+2p | | 6m^3+54m^2-6m=0 | | 4n-9=5+3n | | .25q+0.10(2q+6)=7.35 | | p+16p-15=0 | | 5(x-1)-2(x+2)=3 | | 5(4-2c)+3(c+9)=12 | | 4x/5-x/1=x/10-6/2 | | x+(7x-18)=90 | | 4x-2=12x-38 | | 3(1x+2)=1/4 | | p(x)=4x^3+6x^2-22x-12 | | 3(x-1)+5(x+1)=18 | | 8+5(s-2t)= | | 2(4)=4x | | 2(2)=4x | | 2(0)=4x | | 35000.00+1680.00x=300440.00 |

Equations solver categories